Psychological Resilience and Posttraumatic Growth: An Exploratory Analysis. (September 2019) - Ewert, Alan; Tessneer, Sharon
Background: Epidemiological studies indicate that a majority of the U.S. population has been exposed to at least one traumatic event in their lives. In addition, resilience has become a variable of increasing interest in both society and the field of experiential education (EE).Purpose: In this study, the relationship between psychological resilience, posttraumatic growth (PTG), and participation in EE activities is examined.Methodology/Approach: To measure semester-long changes in resilience, the Connor–Davidson Resilience Scale was used at the beginning and end of an EE program and four different comparison groups. Using the Posttraumatic Growth Inventory (PTGI) and focusing on a 3-week portion of that EE program, PTG was measured using a pre/post format.Findings/Conclusions: Results indicated that EE programming is effective at building resilience but less so for PTG. In addition, no significant differences were noted between females and males on the PTGI scale.Implications: The results of this exploratory study increase our understanding of what psychological changes occur during a semester-long adventure-based EE curriculum with a 3-week high-intensity experience embedded in the program.